2016
DOI: 10.1371/journal.pone.0166817
|View full text |Cite
|
Sign up to set email alerts
|

Weight Gain in Survivors Living in Temporary Housing in the Tsunami-Stricken Area during the Recovery Phase following the Great East Japan Earthquake and Tsunami

Abstract: IntroductionSurvivors who lost their homes in the Great East Japan Earthquake and Tsunami were forced to live in difficult conditions in temporary housing several months after the disaster. Body weights of survivors living in temporary housing for a long period might increase due to changes in their life style and psychosocial state during the medium-term and long-term recovery phases. The aim of this study was to determine whether there were differences between body weight changes of people living in temporar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…The degree of housing damage experienced by survivors could be associated with the ongoing effects of the disaster, including displacement. The extant literature examining health effects after a natural disaster have mainly used data from a single time point and focused on survivors living in temporary housing [ 14 , 18 , 19 ]. Moreover, no studies have clarified the differences in lifestyle and psychosocial factors associated with frailty according to the impact of disaster damage.…”
Section: Introductionmentioning
confidence: 99%
“…The degree of housing damage experienced by survivors could be associated with the ongoing effects of the disaster, including displacement. The extant literature examining health effects after a natural disaster have mainly used data from a single time point and focused on survivors living in temporary housing [ 14 , 18 , 19 ]. Moreover, no studies have clarified the differences in lifestyle and psychosocial factors associated with frailty according to the impact of disaster damage.…”
Section: Introductionmentioning
confidence: 99%
“…By Japanese law, PHs must be used within 2 years6; however, the period was unavoidably extended in the case of the GEJE. After the Great Hanshin Awaji Earthquake in Japan in 1995, it took 5 years for all evacuees to move out of the PHs 31. The GEJE caused more serious damage, so we assumed that there were greater delays in reconstruction, resulting in prolonged PH stays.…”
Section: Discussionmentioning
confidence: 99%
“…insulated with poor airtightness, and were not sufficiently cold-resistant. 25 However, since more recent temporary homes have come equipped with properly insulated walls and double-glazed windows, they are much more airtight and less subject to intraday temperature differences. Over the long-term following a disaster, our results indicated that appropriate temporary housing could be better for avoiding excessive winter SBP surge compared with older occupant-owned housing.…”
Section: Discussionmentioning
confidence: 99%